Exploring Cyberbullying: Reporting Practices, Institutional Responses, and Perceptions of Effectiveness - Unaliya, Maitri; Kataria, Yachi; Bhutra, Yuvraj; Chauhan, Rahul; Maseleno, Andino; Isnanto, Rizal (Siber International Journal of Advanced Law (SIJAL), 2024)
This study investigates the experiences and perceptions of individuals regarding cyberbullying, focusing on reporting practices, actions taken after reporting, and the perceived effectiveness of institutional responses in schools, workplaces, and online platforms. Using ANOVA analysis, no significant differences were found across demographic groups concerning these variables. The findings suggest a pervasive lack of reporting, minimal follow-up actions, and general dissatisfaction with institutional efforts to address cyberbullying. These results highlight the need for stronger intervention strategies, improved reporting mechanisms, and enhanced awareness to foster safer digital environments. Future research should focus on the barriers to reporting and explore how different cultural and contextual factors influence perceptions of cyberbullying and institutional responses. The global significance of addressing cyberbullying lies in its potential to improve mental health and digital safety across diverse populations, contributing to a more secure online experience for all.